Stenodus leucichthys ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Stenodus leucichthys (Güildenstädt, 1772). Inconnu. 150 cm (59 in) TL (Reist in Coad and Reist 2018). Arctic Alaska eastward to Anderson River, Northwest Territory, Canada, and southward to northern Bering Sea drainages; Siberia to White Sea and southward to Kamchatka; Caspian Sea drainages (Mecklenburg et al. 2002). Both anadromous (or amphidromous) and freshwater populations. The anadromous form will enter slightly brackish waters (Reist in Coad and Reist 2018). ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 54, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...